Technology-facilitated sexual violence among Italian youths: validation of the technology-facilitated sexual violence victimization scale - Orsolini, Laura; Yılmaz-Karaman, İmran Gökçen; Selvi, Kerim; Reina, Salvatore; Longo, Giulio; Volpe, Umberto (Frontiers in psychiatry, 2024)
Technology-facilitated sexual violence (TFSV), i.e. the use of digital communication technologies for facilitating sexual violence and harassment, represents a concern due to its exponential growth, particularly among youths. Few studies investigated TFSV, mainly due to the lack of a validated assessment tool, such as the TFSV-Victimization scale (TFSV-VS). Our study aimed to investigate the TFSV phenomenon in a sample of Italian young adults (aged 18-24), through the validation of the Italian translated version of TFSV-VS. The study consisted of two phases: 1) validation of the Italian version of TFSV-VS; b) evaluation of TFSV lifetime and during the last 12 months among Italian youths. In our sample, 78.6% and 56.1% of subjects reported a lifetime and 12-months TFSV victimization, respectively. Digital sexual (70.4% and 46.6%), gender and/or sexuality-based harassment (43% and 29.6%) are those most represented. A gendered and sexuality-based pattern in lifetime TFSV was observed, mainly observed among females (p=0.005) and sexual/gender minority (SGM)(p=0.001). Being female ( <0.001) and perceiving low social support ( = 0.030) were associated with higher subjective distress related to traumatic TFSV experiences. Being female ( <0.001), younger ( =0.006) and perceiving low social support ( =0.030) were associated with the highest psychological distress due to TFSV. Italian TFSV-VS shows good psychometric properties. Our findings observed a gendered trend of TFSV, by suggesting TFSV as a phenomenon influenced by SGM belonging.